Oferta y satisfacción del destino Guano, provincia de Chimborazo - Satian Chafla, Blanca Lizeth (2024)
ABSTRACT: Guano is a tourist destination that has an impressive cultural and architectural heritage, its inhabitants make the hand-woven carpets, vayetas, esteras, ropes and shoes made of cow leather, activities that are the economic livelihood of the area, It also enjoys a rich history, its churches and buildings have a colonial style that attracts the attention of many tourists. In addition, to guarantee visitor satisfaction, the municipality of Guano includes training and certification programs for tourism service providers, and also invests in infrastructure. The research design was descriptive and correlational, the type of research was quantitative, documentary and field. The validation of the instruments was through Cronbach's Alpha. The surveys under the Likert scale obtained a positive value, for which a “Historic Route in Guano” is proposed for the diversification of tourism activities in addition to maintaining the quality and tourism development of the areas where these places with greater historical relevance are located. Key words: Offer, Satisfaction, Heritage, History, Training, Certification, Development, Diversification.